Cognitive Dysfunction in Persons with Type 2 Diabetes Mellitus: A Concept Analysis. (June 2020) - Liu, Tingting; Lee, Jung Eun; Wang, Jing; Ge, Song; Li, Changwei
Although cognitive dysfunction is related to type 2 diabetes mellitus (T2DM), the concept has not yet been well defined. The purpose of this study was to define the concept of cognitive dysfunction in persons with T2DM and examine its defining attributes, antecedents, and consequences. Literature was retrieved from 2008 to 2018 by systematically searching the PubMed, CINAHL, and PsycINFO databases. Based on 37 included studies, three defining attributes were identified: cognitive dysfunction is a recognized or unrecognized symptom, is characterized by a subtle decline in one or more cognitive domains, and is accompanied by pronounced structural changes observed in brain imaging. One major antecedent was diabetes-related or diabetes-specific pathological changes. Consequences included interference with diabetes self-management, nonadherence to recommended self-management behaviors, and a higher risk of having hypoglycemic events. The concept analysis provides a theoretical foundation that can be used to guide evaluations and interventions related to cognitive dysfunction in individuals with T2DM.